Antibiotic Susceptibility Pattern of Bacteria Isolated from Birds Droppings in Aliero, Kebbi State, Nigeria - Jabaka, R. D.; Gabriel, P. O.; Nuhu, U. D.; Obi, Chidiebere,; Abdulazeez, A. F.; Ibrahim, M. A. (UMYU Journal of Microbiology Research)
Antibiotic resistant bacteria in bird droppings are an emerging problem of public health concern. This study investigated the antibiotic resistance pattern of some bacteria isolated from different poultry droppings. Twenty grams (20g) of each sample of bird droppings were obtained from chickens, guinea fowls and turkeys. Bacteria were isolated using cultural techniques. Antibiotic susceptibility testing was carried out using disk diffusion methods against the bacterial isolates. The following Gram positive and negative bacteria were isolated; Escherichia coli (26.7%), followed by Enterobacter aerogenes, Klebsiella pneumoniae, Shigella dysenteriae and Staphylococcus aureus (13.3%) respectively, Salmonella spp., Pseudomonas aeruginosa, and S. epidermidis accounted for 6.7% respectively. The Gram negative bacteria showed 100% susceptibility to Streptomycin, Gentamycin and Ciprofloxacin, followed by Chloramphenicol (83.3%), Cotrimoxazole and Perfloxacin (66.7%), Ofloxacin (50%) and the least was Amoxicillin (33.3%). Moreover, the Gram negative bacteria showed highest resistance against Augmentin (66.7%), followed by Ofloxacin (50%), Cotrimoxazole, and Perfloxacin (33.3%), and then least resistance to Chloramphenicol (16.7%).Similarly, the Gram positive bacteria showed 100% susceptibility to Streptomycin, Gentamycin, Ciprofloxacin, Cefuroxime and Perfloxacin. However, the highest percentage resistance was observed against Cotrimoxazole (50%). In conclusion, this study isolated some potentially resistant bacteria from the various samples of bird droppings. Contamination by these bird droppings may endanger the health of animals, humans and the environment as a whole. This study suggests that poultry farmers be educated about the dangers of giving medications to their birds and the significance of safe bird droppings disposal.